School notebook, a tool for supervision - Totoricagüena Barandica, Karmele; Solabarrieta Badiola, Miren Jone (Avances en Supervisión Educativa, 2016)
When we first decided to do a presentation of a paper about the School Notebook, a digital tool created to register the inspection interventions in education centers, we were encouraged by the rising interest and awareness over this tool that has been implemented by the Inspectorates of Education of the Basque Country. Our main goal is to present the school notebook in the current context, considering its origins and understanding that due to the continuous teamwork to be carried out by the future inspectors, the actual notebook will continue evolving to a more complex and advanced scenario. In conclusion, the present paper´s aim is to reflect on and analyze certain elements to open new doors to the inspectorate. Therefore, we are presenting a model we have created to work within our Autonomous Community considering its virtues and potentialities. We are also pointing out some key elements we should improve towards excellence and efficiency within our professional careers.